Association between serologically confirmed COVID-19 infection and cognitive functioning in community dwelling older adults - Serena, Sabatini; Deborah, Pacifico; Anja, Frei; Gwendolyn, Graf; Puhan, Milo A.; Albanese, Emiliano (Frontiers in Neurology, 2023)
Introduction COVID-19 infection can impact the central nervous system, and is often associated with cognitive decline. However, there are no studies linking serologically confirmed COVID-19 infection with objectively assessed cognitive functioning. We explored whether presence of SARS-CoV-2 antibodies account for variability in participants’ scores on a neuropsychological assessment. Methods In this cross-sectional study participants were 657 (mean age = 72.97; SD = 6.07 years; women = 47.7%) individuals randomly selected from the general population of the canton of Zurich and included in the Corona Immunitas study. We conducted serological tests between October 2020 and May 2021 to detect and quantify SARS-CoV-2 antibodies in peripheral venous blood samples. We assessed cognitive function, vaccination status (vaccinated; not vaccinated), number of health conditions, and demographic variables between January and August 2021. We studied the association between seropositivity and global cognitive function and five cognitive domains (language expression, language comprehension, temporal orientation, spatial orientation, and memory) with linear regression models. Based on SARS-CoV-2 antibodies and vaccination status, we stratified participants into three groups: No SARS-CoV-2 antibodies (N = 402); SARS-CoV-2 antibodies due to vaccination (N = 218); history of SARS-CoV-2 infection and no vaccination (N = 37). Results In the regression model adjusted for age, sex, educational level, and number of health conditions, compared to those without SARS-CoV-2 antibodies, those with SARS-CoV-2 antibodies due to vaccination had better global cognitive functioning (Standardized beta = 0.10; 95% CI = 0.02; 0.17), and those with SARS-CoV-2 antibodies due to infection had poorer cognitive functioning (Standardized beta = −0.10; 95% CI = −0.18; −0.03). Regarding cognitive domains, compared to those without SARS-CoV-2 antibodies, those with SARS-CoV-2 antibodies due to infection scored more poorly on language comprehension and temporal orientation, and those with SARS-CoV-2 antibodies due to vaccination scored better on memory. Discussion By linking serologically confirmed presence of SARS-CoV-2 antibodies to poorer global cognitive functioning in community dwelling older adults we strengthen existing evidence in support of cognitive decline related to COVID-19. Given the large number of infected older adults, and the endurance of the pandemic, our results highlight the need to address COVID-19 related cognitive decline in the clinical and public health areas of prevention, diagnosis, and treatment.